ACTIONES LIBERAE IN CAUSA - Spalević, Žaklina (Law - Theory and Practice, 2010)
The thesis deals with the problem of responsibility for actione liberae in causa. Namely, in order for the existence of the institute of actione liberae in causa certain conditions are needed: (1) that the perpetrator has brought himself into the state of temporary incompetence, (2) that the perpetrator has brought himself into a state of temporary incompetence, or incapacity of judgment and of decision making, with the use of alcohol, drugs, or with some other means, (3) that the perpetrator has performed a felony while in a state in which he didn’t have the ability of judgment and of decision making, (4) that there exists a causal relationship between the action with which the perpetrator has brought himself into the state of temporary incompetence and consequence which it produced. Since the institute of actione liberae in causa represents an exception which considerably differs from general rules on criminal responsibility, it can exist only if all the above mentioned conditions are satisfied. The institute of actiones liberae in causa carries the label of being current and timeless in the field of criminal law, because it is not only based on the scientific achievements of criminal law, but also of medicine, psychology, pharmacy, toxicology, and especially alcohology. Since these sciences undergo a constant development, a question arises, whether the final solution to the institute of actiones liberae in causa can be given. The latest improvement related to this institute was introduced in the new Code on criminal procedure, and it states that the guilt in performed incompetence is determined according to the time immediately before reaching that state. The institute actiones liberae in causa is not applied in cases of substantially decreased level of competence, nor could the perpetrator be mildly sentenced because of that. There is no institute of actiones liberae in causa even if the perpetrator has brought himself into the state of incompetence under the effect of coercion, delusion, or because of onset of pathological intoxication. There ate three types of actiones liberae in causa: deliberate, premeditated and negligent. Our legislation doesn’t recognize deliberate, but only premeditated and negligent. An activity performed in a state of premeditated incapacity is always punished, while a negligent one only when the law precisely anticipates it, and even then through the general regulations on responsibility.